Efficacy of an intervention to increase therapeutic adherence in patients with secondary prevention for cardiovascular disease: a study protocol for a randomized controlled trial - Francisco Manuel Lidón-Muñoz; José Antonio Quesada; José Antonio Quesada; José Antonio Quesada; Vicente Francisco Gil-Guillén; Vicente Francisco Gil-Guillén; Vicente Francisco Gil-Guillén; Domingo Orozco-Beltrán; Domingo Orozco-Beltrán; Domingo Orozco-Beltrán (Frontiers in Medicine)
IntroductionCardiovascular diseases represent the leading cause of mortality worldwide. This category includes cerebrovascular disease, ischemic heart disease, and peripheral vascular disease. Secondary prevention is effective for patients with a history of cardiovascular events, with antihypertensives, statins, and acetylsalicylic acid being the most prescribed drugs. Therapeutic adherence is crucial, as the lack of it increases morbidity, mortality, reduces quality of life, and raises healthcare costs. However, less than half of patients adhere to all three drugs within the first year post-event. Furthermore, non-adherence is more pronounced in primary care.ObjectiveBased on our hypothesis that in patients undergoing cardiovascular secondary prevention, an intervention grounded in the application of the Chronic Care Model improves adherence to the three preventive drugs, this study aims to evaluate the efficacy of a health education intervention, which implements this model, to increase adherence in patients with cardiovascular disease.MethodsAn open-label randomized controlled trial will be conducted, selecting patients who meet inclusion criteria through consecutive non-probability sampling. Random assignment will be performed using the random number table method. Based on a therapeutic adherence rate of 50% in the control group and 80% in the intervention group, with a type I error of 5% (95% confidence interval), a type II error of 20% (80% power), and accounting for a 15% loss to follow-up, the final sample size will be of 45 patients per group. Follow-up will last for 1 year. Following data collection, univariate, bivariate, and multivariate analyses will be performed to isolate confounding factors and assess the intervention’s impact on adherence.DiscussionIf the results obtained in this study are favorable and the intervention is successful in enhancing therapeutic adherence, its applicability would be substantial, representing a feasible intervention for implementation in primary care. This approach addresses a significant public health issue, namely the lack of therapeutic adherence and its associated consequences. Moreover, this is particularly pertinent for high-risk patients, such as those in secondary prevention, given that cardiovascular disease remains the leading cause of mortality in developed countries. This trial has been registered at clinicalTrials.gov, https://clinicaltrials.gov/study/NCT06510946.